Analysis of novel melphalan hydrolysis products formed under isolated lung perfusion conditions using liquid chromatography/tandem mass spectrometry. (4th March 2013) - Boschmans, Jasper; de, Ernst; Van Schil, Paul; Lemière, Filip
<x xml:space="preserve">Abstract</x> RATIONALE Melphalan is a widely used cytotoxic agent in cancer treatments. This phenylalanine analog has been shown an effective drug in the treatment of breast cancer, multiple myeloma and melanoma of the extremities. A good knowledge of the drug's degradation and metabolism are crucial for understanding its activity during cancer treatments. METHODS The formation of hydrolysis products of melphalan is studied using ultra‐performance liquid chromatography (UPLC) tandem mass spectrometry (MS/MS). Aqueous melphalan solutions were incubated at elevated temperatures and analyzed by UPLC/MS/MS. Two previously described hydrolysis products, mono‐ and dihydroxymelphalan (MOH and DOH), were formed in vitro and could be characterized during MS/MS and high‐resolution experiments. RESULTS Novel compounds with m/z values >500 Da were discovered. Comparison of the fragmentation patterns of these new molecules with those of MOH and DOH show great similarities. The higher masses are explained by the presence of two or more melphalan units. In total, more than 15 new hydrolysis products were found. Experiments were set up to study the formation and the chemical structures of these molecules. CONCLUSIONS The hydrolysis of melphalan is studied in the scope of a phase II clinical trial (isolated lung perfusion, ILuP). Patient samples were screened for the presence of all documented and novel melphalan hydrolysis products. This study reports the formation of a new class of oligomeric compounds in both in vivo and in vitro samples. Copyright © 2013 John Wiley & Sons, Ltd.